2009
DOI: 10.1002/art.24175
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the catechol‐O‐methyltransferase gene is associated with osteoarthritis‐related pain

Abstract: The separability between overall and internal motions is evaluated over multiple folding trajectories of the villin headpiece subdomain. The analysis, which relies on the Prompers‐Brüschweiler separability index, offers a potentially useful perspective on protein folding. The protein is considered folded in this study, not when it reaches some static target, but rather when it tumbles as a dynamically constrained object. The analysis also demonstrates how the separability index, when applied to protein folding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 52 publications
1
46
1
2
Order By: Relevance
“…There are at least five sets of genes that have shown to both change an individual's pain sensitivity and increase their likelihood of developing one or more chronic pain states, including catechol-O-methyltransferase (COMT) (an estrogen-sensitive enzyme that may play a more prominent role in females), a number of sodium channel mutations, guanosine triphosphate (GTP) cyclohydroxylase, types 2 and 3 adrenergic receptors, and a potassium central nervous system channel gene (KCNS) [13e18]. These are the genes have been most consistently shown to confer a higher risk of pain sensitivity or the development of chronic pain, but not all studies have confirmed these findings [14,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…There are at least five sets of genes that have shown to both change an individual's pain sensitivity and increase their likelihood of developing one or more chronic pain states, including catechol-O-methyltransferase (COMT) (an estrogen-sensitive enzyme that may play a more prominent role in females), a number of sodium channel mutations, guanosine triphosphate (GTP) cyclohydroxylase, types 2 and 3 adrenergic receptors, and a potassium central nervous system channel gene (KCNS) [13e18]. These are the genes have been most consistently shown to confer a higher risk of pain sensitivity or the development of chronic pain, but not all studies have confirmed these findings [14,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has more recently been shown that these polymorphisms are not specific to FM but also play a role in causing many other chronic painful conditions. In a large series of patients with hip OA, van Meurs et al found that the presence of the 158Met variant of catechol-O-methyltransferase (COMT) triples the risk of developing pain regardless of its radiological grading (73).…”
Section: N the Role Of Geneticsmentioning
confidence: 99%
“…In contrast to these findings, the M allele of rs4680 has been associated with an increased risk of hip pain in a Dutch population-based cohort. The M allele was also associated with increased risk of hip pain among women with radiographic hip osteoarthritis [25], suggesting that COMT may influence how pain is perceived in osteoarthritis.…”
Section: Catechol-o-methyltransferase (Comt)mentioning
confidence: 99%